(untitled) (Kronika Bydgoska, 2010)
After regaining independence in 1920, Bydgoszcz became a city that changed its ethnic naturę from German into Polish. In spite of the ąuick re-Polonisation of the city, the German minority played a significant role. Among all the local minorities, the Gennans werc the most numerous and the best organised. The change of the status of the Germans into an ethnic minority caused bitterness about peace regulations. It was conducive to the emergence of an anti-Polish atmosphere and development of a nationalistic attitude. The mouthpiece for this atmosphere was the reminiscence of professor Martin Staemmler from the University of Wrocław, brother of doctor Siegfried Staemmler, famous in Bydgoszcz, killed during the so-called march to Łowicz. His report on his stay in, among others, Bydgoszcz in 1937 is a special document recalling the atmosphere and opinions of the local Gennan minority. It presents the opinions and the assessment of the situation of the Germans in Wielkopolska and Pomerania Regions heard during his stay in Bydgoszcz, among others. However, it lacks his own opinion, and commonplace opinions of purely propaganda character are dominant.